METHODOLOGY FOR THE DEVELOPMENT OF PHYSICAL QUALITIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
All teaching methods are based on physical education and training, as a result of which a certain level of skill is achieved. Greed refers to a force that is proportional to its strength and greed, and greed refers to a force that is proportional to its strength and the force it exerts on the body.